Magnetic resonance imaging with ultrashort TE (UTE) PULSE sequences: technical considerations. - Tyler, D; Robson, M; Henkelman, R; Young, I; Bydder, G (2007)
It is now possible to detect signals from tissues and tissue components with short T(2)s, such as cortical bone, using ultrashort TE (UTE) pulse sequences. The background to the use of these sequences is reviewed with particular emphasis on MR system issues. Tissue properties are discussed, and tissues are divided into those with a majority and those with a minority of short T(2) components. UTE pulse sequences and their variants are described and clinical applications are illustrated. System design requirements for sequences of this type, including gradient performance, RF switching, and data-processing issues, are outlined.